Standoff attacks by plan on South African security force bases during SWA/Namibian "Bush War" (1966-1989) - Jansen van Rensburg, Wikus (Faculty of Humanities, University of the Free State, 2013)
After World War I (1920), South Africa (SA) was granted a Class C-mandate by the League of Nations to administer the affairs of South West Africa (SWA) (now Namibia). During the middle sixties (1966) and early seventies (1972), the South West Africa Peoples Organisation (SWAPO), through its’ armed military wing – the Peoples Liberation Army of Namibia (PLAN), started resisting through military means by executing armed assaults on the South African Police (SAP) and civilians. This escalated to such an extent that the South African Defence Force (SADF) was tasked to take over the northern border protection during 1974. The armed resistance by PLAN was typical of guerilla warfare and included numerous standoff attacks on the SADF, the SAP and South West Africa Police (SWAPOL) bases. Although numerous actions typical of guerilla warfare, like ambushes, hit-and-run attacks, land-mine incidents, acts of sabotage and intimidation of the local population were launched in SWA/Namibia during the Bush War, this article mainly focuses on standoff attacks by PLAN on SADF/SAP/SWAPOL bases and the kraals of tribal chiefs protected by local militia within SWA/Namibia. These types of attack were typical of guerilla warfare tactics. Other types of guerilla warfare tactics are briefly referred to. More than 161 standoff attacks on the SADF/SAP/SWAPOL bases were launched by PLAN over the 23 year period of the Bush War. Measured against the “attack the rear areas of the enemy to exhaust and to demoralise them” tactic of guerilla warfare, one can hardly claim that PLAN were successful in doing so.
Keywords: Revolutionary warfare; Guerilla warfare; South West Africa People’s Organisation (SWAPO); People’s Liberation Army of Namibia (PLAN); South African Defence Force; Standoff attacks; Sabotage; Ambushes